Limpopo Basin Development Challenge - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2012)
Limpopo Basin The Limpopo is a relatively dry basin and most water in the more productive areas is already claimed. Rainfall is highly variable and in many parts of the basin there is little run-off with which to produce crops and livestock. The basin is a water-scarce environment in which recurring drought and floods cause devastating impacts on the livelihoods of small-scale, subsistence farmers. However, the more pressing development challenge in these farming systems is the unproductive use of water in the more normal rainfall seasons which are much more prevalent.